1998
DOI: 10.1177/155335069800500308
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Liver Resections

Abstract: The authors present the rationale of the laparoscopic approach to liver surgery, showing the technique of fully endoscopic and endoscopic-assisted formal and wedge hepatic resections and the early results of their experience. From 1993 to 1997, 38 liver resections have been attempted through the laparoscopic or the laparoscopic assisted approach. Out of these 38 resections, 5 were wedge resections, 11 were segmentectomies, 10 were left formal hepatectomies, 1 was an extended left hepatectomy, 5 were bisegmente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 2 publications
1
73
1
Order By: Relevance
“…The development of staplers and the harmonic stapler in particular have extended the indications for laparoscopic procedures. Several case reports or small series have been published [25][26][27][28]. However, minimally invasive resection of the liver has lagged behind that of other organs for the following reasons: 1) Many areas of the liver are difficult to access because of the liver's position high in the abdomen posterior to the ribs.…”
Section: Laparoscopic Staging and Laparoscopic Hepatectomymentioning
confidence: 99%
“…The development of staplers and the harmonic stapler in particular have extended the indications for laparoscopic procedures. Several case reports or small series have been published [25][26][27][28]. However, minimally invasive resection of the liver has lagged behind that of other organs for the following reasons: 1) Many areas of the liver are difficult to access because of the liver's position high in the abdomen posterior to the ribs.…”
Section: Laparoscopic Staging and Laparoscopic Hepatectomymentioning
confidence: 99%
“…1,2 Laparoscopic liver resection was first reported in 1992, 3 but unlike other areas of abdominal surgery, this approach has been developed in a very limited number of institutions. [4][5][6][7][8][9][10] Except for a few studies, most of the articles reported a limited number of patients, but it has been established that in select patients, laparoscopic liver resections, if performed in institutions with expertise in hepatic surgery and advanced laparoscopic procedures, are safe, with results identical to those of open surgery. [5][6][7][8][9]11,12 Resection for benign liver disease can represent a valid indication for the laparoscopic approach because of the absence of risk of tumoral dissemination.…”
Section: Ost Indications Formentioning
confidence: 99%
“…5,8,21,29 Although most resections in this series were fewer than 3 segments, 8 major hepatectomies were performed for benign disease (16%). Three of the 4 conversions occurred during major resection, for a 37% conversion rate in major resections (2 were for bleeding and 1, for doubt on tumor limits in a patient with multiple adenomas).…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there have been a few reports of therapeutic laparoscopic liver operations, but most of the reports are limited to wedge resections [6,7]. However, successful larger hepatic resections have recently been reported in humans [8,9,10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%